HOW ORGANISATIONAL CULTURE WITHIN AUSTRALIA’S DEPARTMENT OF HOME AFFAIRS AFFECTS COMPLIANCE WITH THE REFUGEE CONVENTION-A METHODOLOGICAL CONTRIBUTION TO THE LEGAL RESEARCH TRADITION - Revulge, Kamal Kithsiri Karunadasa Hewawasam (PEOPLE: International Journal of Social Sciences, 2019)
This paper describes and analyses the suitability of an auto-ethnographic approach as a data collection method for a legal research study. The present study centred on current Australian asylum and refugee decision-making process and the application of procedural fairness (PF) in complying with 1951 Refugee Convention (RC) and the 1967 Protocol by the Department of Home Affairs (DHA). The researcher uses qualitative research methods for this study and developed an approach using his own experience in the industry as a Migration Lawyer for data collection. In the methodology, he will argue the importance, ethical considerations and relevance of this method as a worthwhile research practice to investigate the visa decision-making process of the DHA. The study aims to gain insight into the complexity and realities of the current DHA asylum and refugee decision-making process and the researcher primarily argues that if Australia claims it supports and protects asylum seekers and refuges and respects human rights, Australia should do so consistently with international human rights standards. However, it is pointed out in the literature that the DHA has issues within its organisational culture (OC); these, the researcher suggests, may impact upon its PF and decision-making of the DHA.Use of auto-ethnographic methods are very rare in legal research studies and by using this method the researcher is making a methodological contribution to the body of knowledge of law, as no similar study carried out in socio-legal studies in the past relating to the Australian Migration industry. This paper specifically discusses about various steps of preparation used by the researcher to overcome obstacles and challenges he faced in the use of his own experience by being an ‘insider’ in researching industry and its implementation in legal research.